Clinical Observation of Silicon Hydrogel Contact Lens Fitted Immediately after Small Incision Lenticule Extraction (SMILE) - Jifang Wang; Shuxin Xi; Bingjie Wang; Zhi Chen; Ke Zheng; Xingtao Zhou (Journal of Ophthalmology)
Purpose. To examine the immediate use of bandage contact lenses (BCLs) for improving patient comfort after small incision lenticule extraction (SMILE) surgery. Methods. This is a prospective randomized controlled study in which one hundred and seventy-eight patients undergoing SMILE were randomly allocated to three groups: group A wore BCLs for 8 hours postsurgery, group B wore BCLs for 24 hours postsurgery, and group C did not wear any BCLs postsurgery. Eight subjective symptoms including photophobia, tearing, pain, foreign body sensation, burning, blurred vision, sting, and dry eyes were prospectively evaluated at 2 hours, 4 hours, 8 hours, and 24 hours, using a questionnaire with a total score of 24. The scores of symptoms and signs were compared between the three groups. Results. There was a statistically significant time effect on scoring, which implicated a decline in symptoms over time after surgery (P<0.001). There was also a significant interaction between time and the treatment group (P<0.01). The total symptom score of groups A and B (5.85 ± 3.97 and 5.99 ± 4.67, respectively) was significantly lower than that of group C at 2 hours postsurgery (7.35 ± 4.86, P<0.05), especially in tearing and pain (P<0.05). The level of corneal oedema at 24 hours postsurgery was also statistically significantly different between the three groups (P<0.001), and the post hoc test showed that groups A and B were lower than group C (P<0.01). Conclusion. Silicon hydrogel BCLs applied immediately after SMILE surgery can relieve postsurgical symptoms of tearing and pain, improving overall patient comfort, and reduce corneal oedema. This trial is registered with ChiCTR-ONRC-13003114. Precis. The application of silicone hydrogel bandage contact lenses immediately after SMILE surgery has the potential to improve patient comfort, corneal healing, and patient satisfaction following SMILE.